Frequency of Hyperuricemia in Tuberculosis patients during Intensive Phase of Therapy - Sajjad Ali, Fazli Rabbi, Ashfaq ur Rehman (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency and pattern of hyperuricemia, including symptomatic and asymptomatic presentations, among tuberculosis patients receiving pyrazinamide as part of first-line anti-tuberculous therapy. Methods: A cross-sectional study was conducted at the department of pulmonology of a tertiary care hospital from September 2022 to February 2023, 155 patients diagnosed with pulmonary or extra-pulmonary tuberculosis and treated with a standard regimen containing pyrazinamide. Serum uric acid levels were measured at 4, 6, and 8 weeks. Hyperuricemia was defined as uric acid greater than 6.6 mg/dL. Patients were clinically evaluated for symptoms related to hyperuricemia. Demographic factors, weight, and TB type were analyzed for association with biochemical elevations. Results: The mean age of patients was 28.9 ± 12.5 years, and females comprised 52.9% of the cohort. Hyperuricemia developed in 136 (87.7%) patients, of whom most were asymptomatic, while 20 (12.9%) experienced symptomatic hyperuricemia presenting with mild arthralgia not requiring treatment modification. Mean serum uric acid levels rose progressively from 3.3 mg/dl at week 4 to 5.5 mg/dl at week 6 and 7.8 mg/dl at week 8. Hyperuricemia occurred in 85% of pulmonary TB, 87.8% of extra-pulmonary TB, and nearly all retreatment cases. No significant variation in hyperuricemia was observed across age, gender, or weight groups, indicating a uniform pharmacological effect of pyrazinamide. Conclusion: Hyperuricemia is highly prevalent among TB patients receiving pyrazinamide, although symptomatic cases remain limited. The consistent rise in serum uric acid across demographic and disease subgroups highlights the predictable nature of pyrazinamide-induced hyperuricemia, emphasizing the importance of biochemical monitoring, particularly in retreatment patients. Keywords: Tuberculosis, Pyrazinamide, Hyperuricemia, Adverse drug reaction, Serum uric acid.